Body fluid absorbent articles

A cellulose fiber-based surface material with cationized starch and specific oils addresses the issues of abrasion resistance and spot absorbency in body fluid absorbent articles, enhancing durability and fluid containment.

JP7605449B2Active Publication Date: 2024-12-24ZUIKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020129737
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-30
Publication Date
2024-12-24
Estimated Expiration
2040-07-30

AI Technical Summary

Technical Problem

Existing body fluid absorbent articles, such as sanitary napkins, lack sufficient abrasion resistance and effective spot absorbency for body fluids, leading to potential tearing and spread of fluids during use.

Method used

A surface material composed of cellulose fibers entangled with cationized starch and specific oils, such as lipophilic glyceryl monostearate and polyoxyethylene lauryl ether, is used, with cationized starch applied at 3-5% and oils at 0.3-1.5% by weight, enhancing fiber bonding and absorbency.

Benefits of technology

The surface material exhibits improved abrasion resistance and spot absorbency, reducing tearing and fluid spread, ensuring comfort and effectiveness during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605449000001
    Figure 0007605449000001
Patent Text Reader

Abstract

To provide a body fluid absorbing article including a surface material which is excellent in abrasion resistance, hard to break at use, and excellent in spot liquid absorption of body fluid.SOLUTION: A body fluid absorbing article comprises a surface material 1, a liquid absorbing body 3 and a leakage preventing material 4 arranged in the order from a body fluid exudation side. The surface material 1 has cotton fibers as the constituent fibers, and comprises a nonwoven fabric in which cotton fiber intervals are entangled. The nonwoven fabric is applied with cationized starch and an oil solution. There are used as for the oil solution: an oil solution containing lipophilic mono stearic acid glyceryl, and polyoxyethylene lauryl ether; an oil solution containing stearic acid amide and a hardened tallow oil; or an oil solution containing stearic acid amide and a palm oil. An application amount of the cationized starch is 3-5 wt.% based on a nonwoven fabric weight, and an application amount of the oil solution is 0.3-1.5 wt.% based on the nonwoven fabric weight. The liquid absorbing body 3 comprises an aggregate of pulp fibers, and the leakage preventing material 4 comprises a body fluid-impermeable synthetic resin film.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a body fluid absorbent article such as a sanitary napkin or a disposable diaper. [Background technology]

[0002] Body fluid absorbent articles such as sanitary napkins are composed of a surface material, a liquid absorbent, and a leakproof material arranged in this order from the body fluid exudation side. Since the surface material comes into direct contact with the skin, a nonwoven fabric made of cellulosic fibers such as cotton fibers, which feel good against the skin, is used. The applicant of the present application has proposed a surface material in which stearic acid amide is added to such a nonwoven fabric in order to make the nonwoven fabric feel better against the skin (Patent Document 1). Furthermore, the applicant of the present application has proposed a surface material in which a specific oil agent is added to the nonwoven fabric so that the exuded body fluid can be absorbed in a spot manner (Patent Document 2).

[0003] [Patent Document 1] Patent No. 5657916 [Patent Document 2] Utility Model Registration No. 3224098 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0004] The present invention is an improved version of the invention disclosed in Patent Document 2, and its objective is to provide a body fluid-absorbent article having a surface material that is highly abrasion resistant, unlikely to break during use, and has excellent spot absorption properties for body fluids. [Means for solving the problem]

[0005] The present invention solves the above-mentioned problems by using a surface material in which a specific nonwoven fabric is applied with cationic starch and a specific oil. That is, the present invention provides a body fluid absorbent article in which a surface material 1, a liquid absorbent 3, and a leakproof material 4 are arranged in this order from the body fluid exudation side, the surface material 1 being a nonwoven fabric whose constituent fibers are entangled with each other, For bonding the constituent fibers to each otherCationic starch and an oil solution containing lipophilic glyceryl monostearate and polyoxyethylene lauryl ether, and an oil solution containing stearic acid amide and palm oil. For spot absorption of body fluids The present invention relates to a body fluid-absorbing article comprising a nonwoven fabric and an oily agent, the amount of the cationic starch applied being 3 to 5% by weight relative to the weight of the nonwoven fabric, and the amount of the oily agent applied being 0.3 to 1.5% by weight relative to the weight of the nonwoven fabric.

[0006] The surface material 1 used in the present invention is made of a nonwoven fabric containing cellulosic fibers as its constituent fibers. As the cellulosic fibers, cotton fibers or rayon fibers are used. In particular, unabsorbed cotton among the cotton fibers is preferable because the cottonseed oil adhering to the surface of the cotton fibers makes it easier to absorb exuded body fluids in a spot-like manner. As the rayon fibers, short fibers having a fineness of 1 to 10 decitex and a fiber length of 10 to 100 mm are generally used, but long fibers may also be used. The nonwoven fabric may contain a small amount of other types of fibers besides the cellulosic fibers.

[0007] The constituent fibers made of cellulosic fibers are entangled with each other. This bonds the constituent fibers to each other, resulting in a nonwoven fabric with a predetermined strength. The entanglement method is preferably a water flow entanglement method. The basis weight of the nonwoven fabric used in the present invention is 10 to 50 g / m 2 That's about it.

[0008] In the present invention, in addition to the bonding between the constituent fibers by entanglement, the constituent fibers are bonded to each other by cationic starch. Cationic starch is easily attached to cellulosic fibers, and can improve the strength of the nonwoven fabric without adversely affecting the oil agent used in the present invention. Starches have molecular weights ranging from several thousand to several hundred million, but in the present invention, it is preferable to use starches with molecular weights ranging from several thousand to several hundred thousand. When starches with molecular weights of several tens of millions are used, the paste becomes highly viscous and is difficult to apply to the nonwoven fabric. Specifically, wheat starch, potato starch, corn starch, high amylose-containing corn starch, tapioca starch, rice starch, taro starch, etc. are used. As a cationic agent for cationizing these starches, conventionally known diethylaminoethyl chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 2,3-epoxypropyltrimethylammonium chloride, etc. are used.

[0009] The nonwoven fabric used in the present invention further contains a specific oil agent. The specific oil agent is an oil agent containing lipophilic glyceryl monostearate and polyoxyethylene lauryl ether. or The oils containing stearic acid amide and palm oil are used alone or in combination. By using such specific oils, both hydrophilic and water-repellent properties are imparted to the material, allowing it to absorb exuded body fluids in a spot-like manner. The quantitative ratio of lipophilic glyceryl monostearate and polyoxyethylene lauryl ether in the oils or The quantitative ratio of stearic acid amide and palm oil is preferably about the same.

[0010] In order to apply the cationic starch and oil to the nonwoven fabric used in the present invention, they may be applied separately, but generally, a mixture of the two liquids is applied to the nonwoven fabric at once. The mixture can be prepared by any method, but for example, it can be prepared by adding and mixing the oil into a gelatinized cationic starch paste liquid.

[0011] The amount of cationic starch applied is 3 to 5% by weight based on the weight of the nonwoven fabric. If the amount applied is less than 3% by weight, the abrasion resistance decreases. If the amount applied is more than 5% by weight, the feel and flexibility of the nonwoven fabric decrease. Amount of oil applied teeth, The amount is 0.3 to 1.5% by weight based on the weight of the nonwoven fabric. If the amount is less than 0.3% by weight, it becomes difficult to absorb body fluids in spots. If the amount is more than 1.5% by weight, the strength and elongation of the nonwoven fabric decreases.

[0012] The body fluid absorbent article according to the present invention comprises a surface material 1 followed by a liquid absorbent 3. The liquid absorbent 3 is an aggregate mainly composed of pulp fibers. In the present invention, a bulky nonwoven fabric 2 having cushioning properties may be disposed between the surface material 1 and the liquid absorbent 3. By disposing such a bulky nonwoven fabric 2, the surface material 1 feels better against the skin. The bulky nonwoven fabric 2 is thicker than the nonwoven fabric constituting the surface material 1. In addition, it is preferable that the constituent fibers of the bulky nonwoven fabric 2 are hydrophobic fibers other than cellulosic fibers. If hydrophilic fibers such as cellulosic fibers are used, the spot liquid absorbency of the surface material 1 tends to be impaired.

[0013] A leakproof material 4 is disposed next to the liquid absorbent 3. A synthetic resin film impermeable to bodily fluids or the like is used as the leakproof material 4. A fixing device (not shown) such as double-sided adhesive tape may be disposed on the surface (the surface opposite the skin side) of the leakproof material 4. The fixing device is used to fix the bodily fluid-absorbent article to the underwear to prevent it from shifting during use.

[0014] The body fluid absorbent article according to the present invention is suitable for use as a sanitary napkin or a disposable diaper, and can also be used as a wound patch for absorbing blood exuding from a wound. Effect of the Invention

[0015] The body fluid-absorbent article according to the present invention uses a specific surface material, and therefore has the effect that the surface material is not easily torn and can absorb exuding body fluid in a spot manner. That is, during use of the body fluid-absorbent article, the article is not easily torn due to friction with the skin, and the exuding body fluid is not easily diffused in the planar direction along the surface material, so that the article does not feel sticky on the skin and can be used comfortably. EXAMPLES

[0016] Example 1 [Preparation of nonwoven fabric] Bleached cotton (manufactured by Marusan Sangyo Co., Ltd.) with 0.4% by weight of natural oil (cottonseed oil) was prepared. This bleached cotton was passed through an air-lay card to open and accumulate fibers, resulting in a fiber weight of about 35 g / m 2 A fiber web of the above formula was obtained. This fiber web was placed on a mesh support and subjected to hydroentanglement while being transported. Hydroentanglement was performed using a spraying device in which spray holes with a nozzle diameter of 0.1 mm were arranged in a row with a hole interval of 0.6 mm, in the following manner. That is, the fiber web was placed on a 100-mesh support, and a water stream was sprayed twice from the spraying device toward the front surface of the fiber web at a spray pressure of 2.8 MPa, and then the fiber web was inverted and a water stream was sprayed twice toward the back surface of the fiber web at a spray pressure of 2.8 MPa to obtain a fiber fleece. This fiber fleece was placed on a 25-mesh support and subjected to a water stream sprayed twice at a spray pressure of 4.1 MPa using the spraying device to obtain a nonwoven fabric.

[0017] [Preparation of the mixture] A mixture was obtained by adding and mixing an oil agent containing stearic acid amide and palm oil to a cationic starch (starch with a molecular weight of hundreds of thousands) paste liquid. The weight ratio of the cationic starch to the oil agent in the mixture was 6:1.

[0018] [Surface material manufacturing] The above-mentioned mixed liquid was sprayed onto the above-mentioned nonwoven fabric, and then dried at 100°C to obtain a surface material having 3% by weight of cationic starch and 0.5% by weight of oil based on the weight of the nonwoven fabric.

[0019] Example 2 A surface material was obtained by applying 3% by weight of cationic starch and 1.0% by weight of oil relative to the weight of the nonwoven fabric in the same manner as in Example 1, except that a mixture in which the weight ratio of cationic starch to oil was 3:1 was used.

[0020] Example 3 A surface material was obtained in which 3% by weight of cationic starch and 0.5% by weight of oil was applied relative to the weight of the nonwoven fabric in the same manner as in Example 1, except that an oil containing lipophilic glyceryl monostearate and polyoxyethylene lauryl ether was used instead of the oil containing stearic acid amide and palm oil.

[0021] Example 4 A surface material was obtained in which 3% by weight of cationic starch and 1.0% by weight of oil was applied relative to the weight of the nonwoven fabric in the same manner as in Example 2, except that an oil containing lipophilic glyceryl monostearate and polyoxyethylene lauryl ether was used instead of the oil containing stearic acid amide and palm oil.

[0022] Example 5 A surface material was obtained in which 3% by weight of cationic starch and 0.5% by weight of oil were applied relative to the weight of the nonwoven fabric in the same manner as in Example 1, except that a cationic starch paste (starch having a molecular weight of the order of hundreds of thousands) was used instead of the cationic starch paste (starch having a molecular weight of the order of hundreds of thousands).

[0023] Example 6 A surface material was obtained by applying 3% by weight of cationic starch and 1.0% by weight of oil to the nonwoven fabric in the same manner as in Example 2, except that a cationic starch paste (starch having a molecular weight of tens of thousands) was used instead of the cationic starch paste (starch having a molecular weight of hundreds of thousands).

[0024] Example 7 A surface material was obtained by applying 5% by weight of cationic starch and 0.5% by weight of oil relative to the weight of the nonwoven fabric in the same manner as in Example 5, except that a mixture in which the weight ratio of cationic starch to oil was 10:1 was used.

[0025] Example 8 A surface material was obtained by applying 5% by weight of cationic starch and 1% by weight of oil relative to the weight of the nonwoven fabric in the same manner as in Example 5, except that a mixture in which the weight ratio of cationic starch to oil was 5:1 was used.

[0026] Example 9 A surface material was obtained in which 5% by weight of cationic starch and 0.5% by weight of oil were applied relative to the weight of the nonwoven fabric in the same manner as in Example 7, except that a cationic starch paste (starch with a molecular weight of several thousand) was used instead of the cationic starch paste (starch with a molecular weight of tens of thousands).

[0027] Example 10 [Preparation of the mixture] A mixture was obtained by adding and mixing an oil agent containing stearic acid amide and palm oil to a cationic starch (starch with a molecular weight of several thousand) paste liquid. The weight ratio of the cationic starch to the oil agent in the mixture was 50:7. A surface material was obtained in the same manner as in Example 1, except that this mixed solution was used instead of the mixed solution of Example 1, to which 5% by weight of cationic starch and 0.7% by weight of oil were applied relative to the weight of the nonwoven fabric.

[0028] Example 11 A surface material was obtained by applying 3% by weight of cationic starch and 0.5% by weight of oil to the nonwoven fabric in the same manner as in Example 5, except that a cationic starch paste (starch with a molecular weight of several thousand) was used instead of the cationic starch paste (starch with a molecular weight of tens of thousands).

[0029] Comparative Example 1 The nonwoven fabric obtained in Example 1 was used as a surface material without any treatment.

[0030] Comparative Example 2 An oil agent containing stearic acid amide and palm oil was sprayed onto the nonwoven fabric obtained in Example 1, and then dried at 100°C to obtain a surface material having 0.3% by weight of the oil agent relative to the weight of the nonwoven fabric.

[0031] Comparative Example 3 An oil agent containing stearic acid amide and palm oil was sprayed onto the nonwoven fabric obtained in Example 1, and then dried at 100°C to obtain a surface material having 0.5% by weight of the oil agent relative to the weight of the nonwoven fabric.

[0032] Comparative Example 4 An oil agent containing stearic acid amide and palm oil was sprayed onto the nonwoven fabric obtained in Example 1, and then dried at 100°C to obtain a surface material having 0.7% by weight of the oil agent relative to the weight of the nonwoven fabric.

[0033] Comparative Example 5 A paste of pregelatinized starch (starch having a molecular weight of hundreds of thousands) was sprayed onto the nonwoven fabric obtained in Example 1, and then dried at 100°C to obtain a surface material having 3% by weight of pregelatinized starch relative to the weight of the nonwoven fabric.

[0034] Comparative Example 6 [Preparation of the mixture] A mixture was obtained by adding and mixing an oil agent containing stearic acid amide and palm oil to a paste liquid of pregelatinized starch (starch with a molecular weight of hundreds of thousands). The weight ratio of pregelatinized starch to oil agent in the mixture was 10:1. Except for using this mixed liquid instead of the mixed liquid of Example 1, a surface material was obtained in the same manner as in Example 1, to which 3% by weight of pregelatinized starch and 0.3% by weight of oil were applied relative to the weight of the nonwoven fabric.

[0035] Comparative Example 7 A liquid containing a paper strength agent whose main component is polyacrylic acid (salt) was sprayed onto the nonwoven fabric obtained in Example 1, and then dried at 100°C to obtain a surface material having 3% by weight of the paper strength agent relative to the weight of the nonwoven fabric.

[0036] Comparative Example 8 [Preparation of the mixture] A mixture was obtained by adding and mixing an oil agent containing stearic acid amide and palm oil to a liquid containing a paper strength agent mainly composed of polyacrylic acid (salt). The weight ratio of the paper strength agent to the oil agent in the mixture was 10:1. Except for using this mixed liquid instead of the mixed liquid of Example 1, a surface material was obtained by the same method as in Example 1, to which 3% by weight of paper strength agent and 0.3% by weight of oil agent were applied relative to the weight of the nonwoven fabric.

[0037] Comparative Example 9 [Preparation of the mixture] A mixture was obtained by adding and mixing an oil agent containing stearic acid amide and palm oil to a liquid containing a paper strength agent mainly composed of polyacrylic acid (salt). The weight ratio of the paper strength agent to the oil agent in the mixture was 30:7. Except for using this mixed liquid instead of the mixed liquid of Example 1, a surface material was obtained by the same method as in Example 1, to which 3% by weight of paper strength agent and 0.7% by weight of oil agent were applied relative to the weight of the nonwoven fabric.

[0038] The surface materials obtained in Examples 1 to 11 and Comparative Examples 1 to 9 were evaluated for abrasion resistance (number of times) and spot liquid absorption (mm) by the following method. The results are shown in Table 1.

[0039] [Wear resistance (cycles) evaluation] Thirty samples of 293 mm long x 165 mm wide were taken from each of the surface materials obtained in Examples 1 to 11 and Comparative Examples 1 to 9 in random directions. Six of these samples were set in a Gakushin-type friction fastness tester (manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd., model number "RT-300") in accordance with JIS L 0849 to measure abrasion resistance. When setting the sample, a urethane mat was laid under the sample in advance, and the sample was fixed to a fixture attached to the Gakushin-type friction fastness tester so as not to wrinkle. In addition, the surface of the friction terminal was covered with a cloth adhesive tape, and a load of 300 g was applied to the friction terminal so that the cloth adhesive tape and the sample were in contact. Then, the friction terminal was slid back and forth at a speed of 30 times / min, and the number of reciprocations when tears were visible on all six samples was measured. This measurement was performed five times, and the average value was taken as the abrasion resistance (times). If no visible tears were observed in any of the six samples even after the number of reciprocations exceeded 500, the measurement was stopped and the number of reciprocations was set to 500. Therefore, the abrasion resistance (number of reciprocations) was at its maximum value at 500 reciprocations.

[0040] [Evaluation of spot absorbency (mm)] Three test pieces measuring 10 cm x 10 cm were taken from each of the surface materials obtained in Examples 1 to 11 and Comparative Examples 1 to 9. The three test pieces were stacked and placed on a filter paper. 1 cc of blue solution was dropped onto the test pieces and left for 5 minutes. Then, only the top test piece (the test piece that had come into direct contact with the blue solution) was taken out, and the widest vertical length (mm) and widest horizontal length (mm) of the area colored blue were added together to obtain the spot liquid absorbency (mm).

[0041] [Table 1] ━━━━━━━━━━━━━━━━━━━━━━━━━━━━ Abrasion resistance (times) Spot liquid absorption (mm) ━━━━━━━━━━━━━━━━━━━━━━━━━━━━ Example 1 450 61.7 Example 2 424 52.7 Example 3 500 64.3 Example 4 325 50.7 Example 5 175 36.7 Example 6 225 41.7 Example 7 275 30.0 Example 8 400 36.0 Example 9 375 45.0 Example 10 300 51.3 Example 11 150 49.0 Comparative Example 1 125 89.7 Comparative Example 2 50 51.3 Comparative Example 3 25 55.7 Comparative Example 4 25 38.3 Comparative Example 5 500 92.6 Comparative Example 6 90 38.0 Comparative Example 7 475 95.0 Comparative Example 8 75 72.7 Comparative Example 9 175 83.0 ━━━━━━━━━━━━━━━━━━━━━━━━━━━━

[0042] As can be seen from the results in Table 1, the surface materials according to the examples have a well-balanced improvement in abrasion resistance and spot liquid absorbency compared to the surface materials according to the comparative examples. [Brief description of the drawings]

[0043] [Figure 1] 1 is a schematic cross-sectional view of a bodily fluid-absorbent article according to an embodiment of the present invention. [Explanation of symbols]

[0044] 1 Surface material 2 Bulky nonwoven fabric 3 Liquid absorption 4 Leak proof material

Claims

1. A bodily fluid absorbent article having a surface material, a liquid absorbent material, and a leak-proof material arranged in this order from the bodily fluid exudation side, The surface material is a nonwoven fabric having cellulose-based fibers as constituent fibers and having the constituent fibers intertwined with each other, to which is applied cationic starch for binding the constituent fibers with each other, and an oil agent for spot-absorbing body fluids selected from the group consisting of an oil agent containing lipophilic glyceryl monostearate and polyoxyethylene lauryl ether, and an oil agent containing stearic acid amide and palm oil; The amount of the cationic starch applied is 3 to 5% by weight based on the weight of the nonwoven fabric, and the amount of the oil applied is 0.3 to 1.5% by weight based on the weight of the nonwoven fabric.

2. 2. The body fluid-absorbent article according to claim 1, wherein the cellulosic fibers are cotton fibers.

3. 2. The body fluid absorbent article according to claim 1, wherein the absorbent material is an aggregate of pulp fibers.

Citation Information

Patent Citations

  • Absorbent article

    JP2017217066A

  • Items that absorb bodily fluids

    JP3224098U

  • Nonwoven webs treated with fixed mobile materials

    US20040033744A1

  • Absorbent article

    WO2019060515A1